Preparation method and application of polymer-based covalent organic framework film
By growing covalent organic frame membranes in situ on polyacrylonitrile porous membranes, using specific raw materials to regulate structure and chemical microenvironment, the problems of traditional membrane selectivity and flux Trade-off are solved, and high mechanical strength and high selection are achieved monopolyvalent ion separation effect.
Patent Information
- Application Number
- CN202411121479.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional polymer separation membranes have a Trade-off effect between selectivity and flux, and their ion transport channels are disordered and uncertain, making it difficult to effectively block monovalent ions and multivalent ions.
The polyacrylonitrile porous membrane after alkali treatment was used as the substrate, and a continuous covalent organic frame membrane was grown in situ on its surface by reverse diffusion method, and trialdehyde phlogenes and para-phenylenediamine or its derivatives were used as raw materials. , regulates the structure and chemical microenvironment of the membrane to form regular 1D nanochannels to achieve highly selective ion separation.
The prepared polymer-based covalent organic frame film has high mechanical strength, flexibility and high throughput, while achieving high single-multivalent ion selectivity, which is suitable for ion separation, water quality purification and high value-added ion enrichment.
Smart Images

Figure CN119158427A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ion separation, and in particular relates to a preparation method of a polymer-based covalent organic framework membrane and application thereof. Background Art
[0002] In recent years, membrane separation technology has developed rapidly due to its advantages of high separation capacity, low energy consumption, small footprint, easy integration and environmental protection, and has been widely used in food production, biomedicine, gas separation, environmental protection and seawater desalination. Among them, electrodialysis is a membrane separation technology that uses potential gradient differences to drive ion migration to achieve selective ion separation. In recent years, it has been widely used in industrial wastewater treatment, drinking water purification, seawater desalination and salt lake lithium extraction. Its core is a highly selective single and multivalent selective ion separation membrane that can hinder multivalent ions and promote the transmission of monovalent ions. Traditional polymer separation membranes have good mechanical properties, but there is a trade-off effect between selectivity and flux. At the same time, the ion transmission channels formed between polymer chains have strong disorder and uncertainty. This discontinuous microscopic channel often makes it difficult to achieve the ideal goal of transmitting monovalent ions and blocking multivalent ions. With the in-depth study of the mechanism of ion separation, theoretical and experimental results show that the transmission of ions at the nanoscale is affected by many factors. Constructing regular, orderly, and easily controllable nanoscale ion transport channels is of great significance for exploring the characteristics of ion transport behavior and developing high-performance ion separation membranes.
[0003] Covalent Organic Frameworks (COFs) are a class of porous crystalline materials formed by covalent bonds of organic molecules, with highly ordered structures and adjustable pore sizes. They have high porosity, excellent chemical stability, and can form regular, continuous 1D nanochannel structures. In addition, the structure of the precursor and the functional groups carried can be adjusted according to specific application requirements to obtain COFs membranes with different structures and different chemical environments, and different ion channels can be constructed on demand to achieve efficient and selective transport and separation of substances. However, the COFs structure itself has low mechanical strength, and it is difficult to synthesize ion separation membranes for practical applications by simple methods. Summary of the invention
[0004] Based on the problems existing in the above-mentioned prior art, the first object of the present invention is to provide a method for preparing a polymer-based covalent organic framework membrane, aiming to make it have the characteristics of simple preparation, high mechanical strength and good flexibility. The second object of the present invention is to provide the use of the above-mentioned polymer-based covalent organic framework membrane as a monovalent and multivalent selective ion separation membrane, aiming to make it have high monovalent and multivalent ion selectivity while having a high flux.
[0005] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0006] The present invention first provides a method for preparing a polymer-based covalent organic framework membrane, which is characterized by: using a polyacrylonitrile porous membrane treated with alkali to partition a reaction container into two chambers, adding a toluene solution of trialdehyde phloroglucinol monomer into the chamber on one side of the porous membrane polyacrylonitrile, adding an acetic acid aqueous solution of p-phenylenediamine or a p-phenylenediamine derivative into the other chamber, and heating the chamber after sealing to obtain the polymer-based covalent organic framework membrane.
[0007] Furthermore, the alkali treatment is to immerse the polyacrylonitrile porous membrane in a 0.1-2M NaOH solution at 25-80° C. for 0.5-8 hours, thereby hydrolyzing the cyano groups of the polyacrylonitrile into carboxyl groups.
[0008] Furthermore, the concentration of the toluene solution of the trialdehyde phloroglucinol monomer is 0.001-0.01 mmoL / mL, and the concentration of the acetic acid aqueous solution of p-phenylenediamine or p-phenylenediamine derivative is 0.005-0.05 mmoL / mL. By adjusting the concentrations of the two solutions, the thickness of the polymer-based covalent organic framework film COFs layer can be adjusted.
[0009] Furthermore, the p-phenylenediamine derivative is 2,5-diaminotoluene or sodium 2,5-diaminobenzenesulfonate. Using 2,5-diaminotoluene as a raw material can enhance the hydrophilicity of the ion transport channel in the covalent organic framework membrane and promote the entry of hydrated ions into the channel; using sodium 2,5-diaminobenzenesulfonate as a raw material can further enhance the hydrophilicity, increase the charge density of negative charges in the channel, adjust the chemical microenvironment in the channel, promote the diffusion of monovalent ions into the membrane and reduce their transport energy barrier, while increasing the transport energy barrier of multivalent ions and hindering their transport.
[0010] Furthermore, the temperature of the heating reaction is 40-100° C. and the reaction time is 24-120 hours.
[0011] The polymer-based covalent organic framework membrane prepared by the present invention can be used as a monovalent or polyvalent selective ion separation membrane.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0013] 1. The present invention in situ grows a continuous and dense COF selection layer on the surface of a porous polymer substrate in the form of back diffusion, and prepares a variety of polymer-based covalent organic framework membranes with different structures, which can be used as monovalent and multivalent selective ion separation membranes. The covalent organic framework membrane prepared by the present invention has regular 1D nanochannels. By adjusting the structure and charged groups of the amino monomer, the ion separation performance of the covalent organic framework membrane can be regulated, thereby achieving good monovalent and multivalent ion separation performance. The covalent organic framework membrane prepared by the present invention has good application potential in the fields of ion separation, water purification, and high value-added ion enrichment.
[0014] 2. When preparing polymer-based covalent organic framework membranes, the present invention screens different amino monomers, analyzes the effects of channel structure, hydrophilicity, electrostatic effect and other factors on ion transport behavior at the nanoscale, and conducts in-depth performance regulation. The resulting membrane has a high flux and high monovalent and polyvalent ion selectivity.
[0015] 3. The covalent organic framework series membrane prepared by the present invention is a TpPa series membrane, selected from TpPa, TpPa-CH3, TpPa-SO3Na, preferably TpPa-SO3Na. Compared with the membrane with a selective layer of TpPa prepared from trialdehyde phloroglucinol monomer and p-phenylenediamine as raw materials, the use of trialdehyde phloroglucinol monomer and 2,5-diaminotoluene as raw materials (the selective layer TpPa-CH3 of the obtained membrane) can enhance the hydrophilicity of the ion transport channel in the covalent organic framework membrane and promote the entry of hydrated ions into the channel. The use of trialdehyde phloroglucinol monomer and sodium 2,5-diaminobenzenesulfonate as raw materials (the selective layer of the obtained membrane is TpPa-SO3Na) can further enhance the hydrophilicity, increase the charge density of negative charges in the channel, adjust the chemical microenvironment in the channel, promote the diffusion of monovalent ions into the membrane and reduce their transport energy barrier, while increasing the transport energy barrier of multivalent ions and hindering their transport.
[0016] 4. The reaction conditions of the present invention are mild, the preparation method is simple, and the prepared COFs membrane is tightly bonded to the substrate, making it easy to obtain a complete, defect-free ion separation membrane.
[0017] 5. The present invention uses polyacrylonitrile porous membrane as the base membrane, which plays a triple role: on the one hand, it serves as a diaphragm for the reverse diffusion reaction; on the other hand, it serves as a supporting layer to provide certain mechanical properties and support for the TpPa series membranes; on the other hand, the large number of carboxyl groups after hydrolysis provide reaction sites for the precursor, so that COFs and the porous polymer substrate are closely combined. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A reaction device provided in an embodiment of the present invention.
[0019] Figure 2The scanning electron microscope cross-sectional images of three polymer-based covalent organic framework films prepared in the embodiments of the present invention are shown in FIG. Figure 2 (a), (b), and (c) correspond to TpPa prepared in Example 1, TpPa-CH3 prepared in Example 2, and TpPa-SO3Na prepared in Example 3, respectively.
[0020] Figure 3 XRD patterns of three covalent polymer-based covalent organic framework membranes TpPa, TpPa-CH3, and TpPa-SO3Na prepared in embodiments of the present invention.
[0021] Figure 4 The XPS graphs of three covalent polymer-based covalent organic framework films prepared in the embodiments of the present invention are as follows: Figure 4 (a), (b), and (c) correspond to the amide bonds on the COF skeleton structure of TpPa prepared in Example 1, TpPa-CH3 prepared in Example 2, and TpPa-SO3Na prepared in Example 3, respectively, and (d) corresponds to the sulfonic acid group of TpPa-SO3Na prepared in Example 3.
[0022] Figure 5 The water contact angles of three covalent polymer-based covalent organic framework membranes TpPa, TpPa-CH3, and TpPa-SO3Na prepared in embodiments of the present invention.
[0023] Figure 6 This is a diagram of an electrodialysis device used in an embodiment of the present invention.
[0024] Figure 7 The single-component mono / divalent ion separation performance diagrams of three covalent polymer-based covalent organic framework membranes prepared in embodiments of the present invention, wherein (a) is the selectivity between mono- and multivalent cations, and (b) is the flux of mono- and multivalent cations.
[0025] Figure 8 The two-component monovalent / divalent ion separation performance diagram (including selectivity and flux) of three covalent polymer-based covalent organic framework membranes and commercial polyacrylonitrile porous membrane (PAN) prepared in the embodiments of the present invention is shown in FIG. Figure 8 (a), (b), (c), and (d) correspond to PAN, TpPa prepared in Example 1, TpPa-CH3 prepared in Example 2, and TpPa-SO3Na prepared in Example 3, respectively.
[0026] Fig. 9 The transmembrane energy barriers of three covalent polymer-based covalent organic framework membranes and commercial polyacrylonitrile porous membrane (PAN) prepared in the embodiments of the present invention are shown in FIG. Fig. 9(a), (b), (c), and (d) correspond to PAN, TpPa prepared in Example 1, TpPa-CH3 prepared in Example 2, and TpPa-SO3Na prepared in Example 3, respectively. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0028] The reaction apparatus used in the following examples is as follows Figure 1 As shown, it includes two chambers on the left and right and a porous supporting substrate membrane in the middle.
[0029] Example 1
[0030] In this embodiment, the polymer-based covalent organic framework membrane is prepared according to the following steps:
[0031] The commercial polyacrylonitrile porous membrane was cut into a square of 4*4 cm, immersed in a 1M NaOH solution at 40°C for 2 h, and then taken out and repeatedly immersed and washed with deionized water until the aqueous solution was neutral.
[0032] Trialdehyde phloroglucinol (9.8 mg, 0.047 mmoL) was dissolved in 7 mL of toluene to obtain solution A; p-phenylenediamine (7.57 mg, 0.07 mmoL) was dissolved in 7 mL of an aqueous solution of acetic acid (9 M) to obtain solution B.
[0033] The alkali-treated polyacrylonitrile porous membrane was Figure 1 Place it between the two chambers, add solution A to the chamber on the porous membrane polyacrylonitrile side (i.e. the smooth side of the membrane), add solution B to the other chamber, seal it with plastic wrap, put it in an oven, and react at 70°C for 72 hours.
[0034] The prepared polymer-based covalent organic framework membrane, named TpPa, was taken out, soaked and washed three times with 50 mL of methanol and deionized water in sequence, and dried naturally at room temperature.
[0035] Example 2
[0036] In this embodiment, the polymer-based covalent organic framework membrane is prepared according to the following steps:
[0037] The commercial polyacrylonitrile porous membrane was cut into a square of 4*4 cm, immersed in a 1M NaOH solution at 40°C for 2 h, and then taken out and repeatedly immersed and washed with deionized water until the aqueous solution was neutral.
[0038] Trialdehyde phloroglucinol (9.8 mg, 0.047 mmoL) was dissolved in 7 mL of toluene to obtain solution A; 2,5-diaminotoluene (8.55 mg, 0.07 mmoL) was dissolved in 7 mL of an aqueous solution of acetic acid (9 M) to obtain solution C.
[0039] The alkali-treated polyacrylonitrile porous membrane was Figure 1 Place it between the two chambers, add solution A to the chamber on the porous membrane polyacrylonitrile side (i.e. the smooth side of the membrane), add solution C to the other chamber, seal it with plastic wrap, put it in an oven, and react at 70°C for 72 hours.
[0040] The prepared polymer-based covalent organic framework membrane, named TpPa-CH3, was taken out and soaked and washed three times with 50 mL of methanol and deionized water respectively, and dried naturally at room temperature.
[0041] Example 3
[0042] In this embodiment, the polymer-based covalent organic framework membrane is prepared according to the following steps:
[0043] Add 250 mL of deionized water to a round-bottom flask, add 1.882 g of 2,5-diaminobenzenesulfonic acid, and add 0.4 g of NaOH after it is completely dissolved. After the mixture is magnetically stirred at 25°C for 2 hours, pour it into a glass dish and dry it on a hot plate at 70°C to obtain sodium 2,5-diaminobenzenesulfonate for use. Sodium 2,5-diaminobenzenesulfonate is used instead of 2,5-diaminobenzenesulfonic acid because there is a strong interaction between the protonated sulfonic acid group and the amino group in between or within the molecule, which hinders the polymerization reaction of the amino group and the aldehyde group.
[0044] The commercial polyacrylonitrile porous membrane was cut into a square of 4*4 cm, immersed in a 1M NaOH solution at 40°C for 2 h, and then taken out and repeatedly immersed and washed with deionized water until the aqueous solution was neutral.
[0045] Trialdehyde phloroglucinol (9.8 mg, 0.047 mmoL) was dissolved in 7 mL of toluene to obtain solution A; sodium 2,5-diaminobenzenesulfonate (14.7 mg, 0.07 mmoL) was dissolved in 7 mL of an aqueous solution of acetic acid (9 M) to obtain solution D.
[0046] The alkali-treated polyacrylonitrile porous membrane was Figure 1Place it between the two chambers, add solution A to the chamber on the porous membrane polyacrylonitrile side (i.e. the smooth side of the membrane), add solution D to the other chamber, seal it with plastic wrap, put it in an oven, and react at 70°C for 72 hours.
[0047] The prepared polymer-based covalent organic framework membrane, named TpPa-SO3Na, was taken out and soaked and washed three times with 50 mL of methanol and deionized water respectively, and dried naturally at room temperature.
[0048] The polymer-based covalent organic framework membranes prepared in the above embodiments were characterized and tested as follows:
[0049] 1. SEM characterization
[0050] Figure 2 The SEM images of the polymer-based covalent organic framework membranes obtained in each embodiment are shown in the figure. It can be seen from the figure that a COFs selection layer is formed on the top of the polyacrylonitrile porous membrane, and the membrane surfaces of TpPa, TpPa-CH3 and TpPa-SO3Na are continuous, dense and have no obvious defects. The thickness of the COFs selection layer grown on the top of the polyacrylonitrile porous membrane is ~127nm, ~101nm, and ~134nm, respectively. The thickness of the three membrane selection layers is close, and the interference with the subsequent ion separation performance can be ignored.
[0051] 2. XRD characterization
[0052] Figure 3 The XRD diagram of the polymer-based covalent organic framework film obtained in each example shows that the diffraction peaks are located at 4.7°, 8.3°, and 26.7°, which proves that the synthesized COFs layer has good crystallinity.
[0053] 3. XPS characterization
[0054] Figure 4 The XPS graphs of the polymer-based covalent organic framework films obtained in each embodiment show that -CC / -C=C at 284.8 eV, CN bond at 286.2 eV, and -C=O bond at 288.4 eV in the covalent organic framework skeleton structure prove the existence of amide bonds in the skeleton structure. At the same time, the sulfonic acid group S in TpPa-SO3Na is observed. 2p1 / 2 , S 2p3 / 2 The existence of the peak further proves that the sulfonic acid group on sodium 2,5-diaminobenzenesulfonate was introduced into the COF framework, proving that TpPa, TpPa-CH3 and TpPa-SO3Na were successfully synthesized.
[0055] 4. Water contact angle
[0056] Figure 5The water contact angle comparison diagram of the polymer-based covalent organic framework membranes obtained in each embodiment can be seen from the figure: the covalent organic framework membrane based on TpPa shows hydrophilicity, and the covalent organic framework membranes based on TpPa-CH3 and TpPa-SO3Na further improve the hydrophilicity, improve the chemical microenvironment on the surface of the covalent organic framework membrane, which is beneficial to the enrichment of hydrated ions from the solution to the surface of the COF layer, and is beneficial to the subsequent diffusion and migration of ions from the solution into the channel.
[0057] 5. Monovalent and divalent ion separation performance test
[0058] The polymer-based covalent organic framework membrane prepared in each embodiment is used as a monovalent cation selective separation membrane to construct an electrodialysis device, and its membrane stack structure is as follows: Figure 6 As shown, it includes a positive electrode plate, a commercial anion exchange membrane, a polymer-based covalent organic framework membrane, a commercial anion exchange membrane, and a negative electrode plate. The membrane stack forms four compartments: an anode chamber, a desalination chamber, a concentration chamber, and a cathode chamber. The effective area of the membrane that can be passed through by ions in the device is 2.00 cm 2 The electrodialysis experiment was run in constant current mode at a temperature of 25 °C and a current density of 2 mA cm -2 , the test time is 1h.
[0059] Electrodialysis testing is divided into single-component ion system and two-component mixed ion system, as follows:
[0060] Single component ion system: electrode chamber is 100mL 0.3M Na2SO4 solution, desalination chamber is 100mL 0.1M MCl X (M=K, Na, Li or Mg) solution, the concentrating chamber is 100mL of deionized water.
[0061] Two-component mixed ion system: the electrode chamber is 100mL 0.3M Na2SO4 solution, the desalination chamber is 100mL 0.1MMCl / 0.1M MgCl2 (M=K, Na or Li) solution, and the concentration chamber is 100mL deionized water.
[0062] After the test is completed, the solution in the concentration chamber is collected and the cation concentration to be tested is detected by inductively coupled plasma atomic emission spectroscopy (ICP-AES), where the cation flux calculation formula is as follows:
[0063]
[0064] J (mol·m -2 ·h -1 ) represents the cation flux, C t (moL·L -1 ) and C0(moL·L -1) are the concentrations of ions in the concentration chamber at time t and time 0, V(L) is the liquid volume in the concentration chamber, t(h) is the test time, A m (m 3 ) is the effective area of the membrane during the test.
[0065] The selectivity between monovalent and polyvalent cations can be calculated by the following formula:
[0066]
[0067] in: For cation M + and M 2+ The selectivity, and To desalinate indoor cations + and M 2+ concentration.
[0068] The test results of the single-component ion system are as follows: Figure 7 As shown, in Figure 7 (a) The selectivity performance is:
[0069] (1) Li between the three membranes + / Mg 2+ The order of ion selectivity is TpPa-SO3Na>TpPa>TpPa-CH3;
[0070] (2) Na between the three membranes + / Mg 2+ The order of ion selectivity is TpPa-SO3Na>TpPa>TpPa-CH3;
[0071] (3) K between the three membranes + / Mg 2+ The order of ion selectivity is TpPa-SO3Na>TpPa>TpPa-CH 3。
[0072] It can be seen that the polyacrylonitrile substrate membrane itself has almost no selectivity, so the selectivity comes almost entirely from the COFs layer. The preferred TpPa-SO3Na exhibits the best single-component ion separation performance. On the other hand, the three membranes are compared:
[0073] (1) For TpPa membrane, the order of different ion selectivity is S Na+ / Mg2+ >S K+ / Mg2+ >S Li+ / Mg2+ ;
[0074] (2) For TpPa-CH3 membrane, the order of different ion selectivity is S Na+ / Mg2+ >S K+ / Mg2+ >SLi+ / Mg2+ ;
[0075] (3) For TpPa-SO3Na membrane, the order of selectivity of different ions is S Na+ / Mg2+ >S K+ / Mg2+ >S Li+ / Mg2+ ;
[0076] Figure 7 In (b), the flux of monovalent ions conforms to TpPa-SO3Na>TpPa>TpPa-CH3, and Mg 2+ The flux is two orders of magnitude lower than that of monovalent ions.
[0077] Figure 7 The results show that the preferred TpPa-SO3Na exhibits the best single-component ion separation performance, especially the introduction of sulfonic acid groups improves the hydrophilicity of the membrane surface and promotes the enrichment of ions on the membrane surface. At the same time, the strong electrostatic interaction between itself and magnesium ions hinders the transmission of magnesium ions. Therefore, its separation performance is the best, and Na + / Mg 2+ Highest separation performance.
[0078] The test results of the two-component ion system are as follows: Figure 8 As shown in the figure, the same trend as the single-component separation performance is shown. TpPa-SO3Na shows the best two-component ion separation performance, and its + / Mg 2+ On the other hand, it can be seen that Figure 8 In (a), (b), (c), and (d), the magnesium ion flux decreased by 1 to 2 orders of magnitude compared to the single-component separation performance. The results show that the introduction of methyl and sulfonic acid groups, by adjusting the hydrophilicity and regulating the electrostatic interaction, achieved the regulation of ion separation performance. At the same time, under the two-component condition, the interaction between the monovalent ions and the sulfonic acid groups occupied the space inside the 1D channel on the COFs structure, further enhancing its own barrier capacity for magnesium ions and reducing the flux of magnesium ions. Therefore, it can be seen that the selectivity of TpPa-SO3Na has been significantly improved.
[0079] 6. Transmembrane energy barrier
[0080] The test results of transmembrane energy barrier are as follows Fig. 9 , Fig. 9 (a), (b), (c), (d) are Na, Li + 、Na + , K + Mg 2+The transmembrane energy barriers of the four ions when they pass through the polyacrylonitrile porous membrane (PAN), TpPa membrane, TpPa-CH3 membrane, and TpPa-SO3Na membrane. Due to the growth of the COFs selective layer, Fig. 9 In (b), (c), and (d), except for sodium ions, the transmembrane energy barriers of other ions are higher than Fig. 9 (a).
[0081] When hydrated ions pass through a membrane, they go through the process of solution-membrane surface-membrane channel-membrane surface-solution, among which the transport of ions within the membrane is the main component of the transmembrane energy barrier. At this time, the influence of the chemical environment inside the channel on ion transport is dominant.
[0082] From the perspective of hydrophilicity, the introduction of methyl and sulfonic acid groups enhances the hydrophilicity of the membrane surface, effectively promoting the enrichment of hydrated ions from the solution to the surface of TpPa-CH3 and TpPa-SO3Na. Fig. 9 (c) It can be seen that the transmembrane energy barriers of the four ions in TpPa-CH3 are increased compared with those in TpPa membrane. It can be seen that the increase in hydrophilicity hinders the transmission of hydrated ions inside the channel of TpPa-CH3 membrane. Therefore, it can be analyzed that the increase in hydrophilicity is not conducive to ion transmission inside the channel, so the selectivity of TpPa-CH3 is lower than that of TpPa. Compared with TpPa-CH3 membrane, the further increase in hydrophilicity of TpPa-SO3Na membrane should have further increased the transmembrane energy barrier, but the actual test results are completely opposite to the predictions. Therefore, there are other factors that affect ion transmission.
[0083] Electrostatic interaction is another factor that affects ion transport. For cations, negatively charged membranes are conducive to providing a large number of ion binding sites, which promotes the transport of cations within the membrane. For TpPa-SO3Na membranes, sulfonic acid groups are the dominant factor that reduces the energy barrier for monovalent ion transport. The order of interaction between different ions and sulfonic acid groups from strong to weak is: Mg 2+ >>Li + >K + >Na + .from Fig. 9 (d) It can be seen that the transmembrane energy barrier of monovalent ions is low, while that of multivalent ions is high. The negatively charged sulfonic acid groups on the TpPa-SO3Na membrane interact weakly with monovalent cations. At this time, hydrated ions can be transferred between multiple sulfonic acid groups in the 1D channel through the "hopping mechanism" in a "swinging" manner. Therefore, the transmembrane energy barrier is reduced. For multivalent ions, such as Mg 2+ Due to its higher charge number and strong interaction with the sulfonic acid groups, it is difficult for it to migrate away from the sulfonic acid groups on the inner wall of the channel, thus increasing the transmembrane energy barrier.
[0084] The different interaction strengths between different ions and sulfonic acid groups result in a gap between the transmembrane energy barriers between ions. The larger the gap, the higher the corresponding selectivity. Fig. 9 (d) It can be seen that for TpPa-SO3Na membrane, the energy barrier gap between monovalent and divalent ions across the membrane is ΔE Na+ / Mg2+ >ΔE K+ / Mg2+ >ΔE Li+ / Mg2+ , so the selectivity S Na+ / Mg2+ >S K+ / Mg2+ >S Li+ / Mg2+ .
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polymer-based covalent organic framework membrane, characterized in that: The reaction container is divided into two chambers by using a polyacrylonitrile porous membrane treated with alkali, a toluene solution of trialdehyde pyroglucin monomer is added to the chamber on one side of the porous membrane polyacrylonitrile, and an acetic acid aqueous solution of p-phenylenediamine or a p-phenylenediamine derivative is added to the other chamber. After sealing, the chamber is heated for reaction to obtain a polymer-based covalent organic framework membrane.
2. The preparation method according to claim 1, characterized in that: The alkali treatment is to immerse the polyacrylonitrile porous membrane in a 0.1-2M NaOH solution at 25-80° C. for 0.5-8 hours, so as to hydrolyze the cyano group of the polyacrylonitrile into a carboxyl group.
3. The preparation method according to claim 1, characterized in that: The concentration of the toluene solution of the trialdehyde phloroglucinol monomer is 0.001-0.01 mmoL / mL.
4. The preparation method according to claim 1, characterized in that: The p-phenylenediamine derivative is 2,5-diaminotoluene or sodium 2,5-diaminobenzenesulfonate.
5. The preparation method according to claim 1, characterized in that: The concentration of the acetic acid aqueous solution of p-phenylenediamine or p-phenylenediamine derivative is 0.005-0.05 mmoL / mL.
6. The preparation method according to claim 1, characterized in that: The temperature of the heating reaction is 40-100° C., and the reaction time is 24-120 hours.
7. A polymer-based covalent organic framework membrane prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the polymer-based covalent organic framework membrane according to claim 7 as a monovalent or multivalent selective ion separation membrane.
Citation Information
Cited By
Functionalized TpPa-1 covalent organic framework as well as preparation method and application thereof
CN119751787A
